2015
DOI: 10.3168/jds.2014-8836
|View full text |Cite
|
Sign up to set email alerts
|

Effect of replacing alfalfa with panicled-tick clover or sericea lespedeza in corn-alfalfa-based substrates on in vitro ruminal methane production

Abstract: Methane emissions from ruminant livestock contribute to total anthropogenic greenhouse gas emissions and reduce metabolizable energy intake by the animal. Condensed tannins (CT) are polyphenolic plant secondary compounds commonly produced by some perennial forage legumes that characteristically bind to protein, carbohydrates, and minerals. The degree to which CT may affect ruminant nutrition depends upon the concentration, structural composition, and biological activity of the CT. The objective of our experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Quijada et al (2015) demonstrated that CT composed predominately of prodelphinidin subunits had greater anthelmintic activity than those composed predominantly of procyanidin. This may explain why L. cuneata, a forage that produces CT composed predominately of prodelphinidin subunits (Naumann et al, 2015b), has demonstrated high anthelmintic efficacy in vivo (Shaik et al, 2006;Terrill et al, 2007;Terrill et al, 2009). Similar findings have been reported with cattle parasites.…”
Section: The Anthelmintic Activity Of Condensed Tanninsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quijada et al (2015) demonstrated that CT composed predominately of prodelphinidin subunits had greater anthelmintic activity than those composed predominantly of procyanidin. This may explain why L. cuneata, a forage that produces CT composed predominately of prodelphinidin subunits (Naumann et al, 2015b), has demonstrated high anthelmintic efficacy in vivo (Shaik et al, 2006;Terrill et al, 2007;Terrill et al, 2009). Similar findings have been reported with cattle parasites.…”
Section: The Anthelmintic Activity Of Condensed Tanninsmentioning
confidence: 99%
“…It is possible to accomplish this objective with CT. In in vitro rumen fermentation studies, replacement of 45% of the forage portion of a corn-alfalfa diet for either L. cuneata or D. paniculatum, achieving dietary CT concentrations of 2.6 and 9%, respectively, decreased CH 4 production without decreasing total gas production (Naumann et al, 2015b).…”
Section: Ct-enteric Fermentation Interactionsmentioning
confidence: 99%
“…The gas decline by 19.68% when tannin was added at 2% and further decline to maximum 33.63% when the tannin addition was increased into 4% DM In this study though the levels of tannin addition (based on tannin content of leucaena) was higher (6.45% and 3.13% at leucaena hybrid mixture at 50% and 25% respectively the reduction of gas production was lower (13.3% and 21% respectively for mixture at 50 and 25%) the difference of gas production due to tannin addition in the current study with previous study reported by Huang et al (2010) might be caused by the difference of tannin activity in extracted form (Huang et al 2010) or in intact in the plant materials form such in the current study. Naumann et al (2015) also reported that at different level of tannin content and different source of tannin in the diet did not affect total gas production. This indicated that effect of tannins on feed fermentation varied.…”
Section: In Vitro Digestibilitymentioning
confidence: 92%
“…We determined the prodelphinidin:procyanidin ratio of CT from six plants, using anthocyanidin monomers as described by Naumann et al (2015), using purified CT added to butanol acid. Delphinidin and propelargonidin (Sigma-Aldrich Co., St. Louis, MO, USA) were used as standards in HPLC-controlled by Breeze software.…”
Section: Methodsmentioning
confidence: 99%